Expanding Your Traditional Quick Books Course with Labyrinth Learning Digital Tools in an Online Environment - Page, James Kyle (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2018)
This Study focuses on processes and outcomes associated with an accounting faculty initiative to reform teaching and learning in the undergraduate accounting curriculum at a private university. The purpose of this study is fourfold. First, the study examines the preparation for students in the workplace. Second, retention and completion of students. Third, the study examines learning outcomes to improve undergraduate teaching. Lastly, the study aims to develop an understanding of how outcomes of digital tools technology-enhanced reform can serve to alleviate time constraints on accounting faculty and address challenges of faculty in an online environment.